Intercultural reading of the Bible and cultural anthropology: a way back and forth - Zúñiga Valerio, Hanzel José (2023)
This essay proposes, based on the recognition of cultural and religious diversity, that the use of social sciences, particularly social anthropology, is an indispensable tool for the intercultural reading of the biblical text. In the discovery of the Bible as product of conflicting memories, voices and cultures, be conscious of distances is a way of creating bridges between different realities but which, in fact, have always interacted and can discover new paths for humanity in the Bible and beyond the Bible.